Hubungan Kebiasaan Main Game Online dan Pengawasan Orang Tua dengan Kebutuhan Istirahat dan Tidur pada Anak Umur 11-14 Tahun di SMP Tunas Bangsa Depok Tahun 2021 - Hardiyanti, Yuni; Shifa, Nurul Ainul (Health & Medical Sciences, 2023)
Game online are very popular in various circles, one of which is popular among school children. School-age children enter new developments about play and games. Rest and sleep are as important as the need for food, activity, and other needs. The purpose of this study was to find out the relationship between playing online game habits and parental supervision with the need for rest and sleep in children aged 11-14 years at SMP Tunas Bangsa Depok in 2021. This research method is quantitative correlation using a statistical test, namely the Spearman rank test with the SPSS program with a cross-sectional approach using a Likert-scale questionnaire. The population in this study amounted to 240 students and the sample in this study amounted to 71 students. Based on the statistical test results, namely the Spearman rank test, the significance value is sig 0.041 <0,1, so there is a correlation or relationship between the habit of playing online games and the need for rest and sleep at SMP Tunas Bangsa Depok in 2021 and a significance value of .032, if the sig value is 0.032 <0,1, there is a correlation or relationship between parental supervision and the need for rest and sleep at SMP Tunas Bangsa Depok in 2021.